2020
DOI: 10.3389/fcvm.2020.00008
|View full text |Cite|
|
Sign up to set email alerts
|

Protein Subdomain Enrichment of NUP155 Variants Identify a Novel Predicted Pathogenic Hotspot

Abstract: Functional variants in nuclear envelope genes are implicated as underlying causes of cardiopathology. To examine the potential association of single nucleotide variants of nucleoporin genes with cardiac disease, we employed a prognostic scoring approach to investigate variants of NUP155, a nucleoporin gene clinically linked with atrial fibrillation. Here we implemented bioinformatic profiling and predictive scoring, based on the gnomAD, National Heart Lung and Blood Institute-Exome Sequencing Project (NHLBI-ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In terms of the concerns of increasing the risk of adverse cardiovascular outcomes by HIIT in COVID-19 survivors, other reports suggest otherwise ( 48 ). Hence, a recent, admittedly small retrospective study of 28 discharged COVID-19 survivors reported that rehabilitation triggered by HIIT, with endurance training at the maximum tolerated exercise load was both safe and feasible ( 49 ).…”
Section: Hiit: Is It Effective And/or Safe In Covid-19?mentioning
confidence: 99%
“…In terms of the concerns of increasing the risk of adverse cardiovascular outcomes by HIIT in COVID-19 survivors, other reports suggest otherwise ( 48 ). Hence, a recent, admittedly small retrospective study of 28 discharged COVID-19 survivors reported that rehabilitation triggered by HIIT, with endurance training at the maximum tolerated exercise load was both safe and feasible ( 49 ).…”
Section: Hiit: Is It Effective And/or Safe In Covid-19?mentioning
confidence: 99%
“…The global co-and post-transcriptional mechanisms implicated in cardiac fibrosis are not well established, however, emerging studies are geared at extracting the subtle communications to identify intersection points between the cellular stress regulating pathways, regulatory non-coding RNAs, RNA metabolism intermediates/mediators and cardiac RNA binding proteins (RBFox, HuR, MBNL2, PUM2, QKI, CELF1, MBNL1, PTBP1) in context of cardiac diseases including fibrosis [66,[112][113][114][115][116][117][118][119][120]. A recent study implicated NUP155 subdomain hotspot with enriched allelic variants of the gene that suggests important role of RNA metabolism in cardiac disease and development [121].…”
Section: Messenger Rna Regulatory Network May Modulate Cellular Strementioning
confidence: 99%
“…Immunostimulatory RNAs (like double stranded RNAs) generated through deregulated RNA processing pathways along with RNA binding proteins of RNA helicase (RNA sensors) family are emerging as important components of immune response pathways during sterile inflammation that involves DAMP sensing [15,16]. Mitochondrial quality control pathways intersecting with the endosomal compartments and lysosomes are recently reported to favor generation and release of mitochondrial-derived vesicles in former condition [143], further offering discernible biologically stable lipid vesicles that may help investigate how secreted cargos can impact tissue repair and homeostasis or trigger fibrosis, and can be extended to establishment of liquid biopsies for studying the progression of fibrotic diseases or alternatively these vesicles may serve as therapeutic tools like exosome-derived non coding RNAs [121,125,127,128,138,139,141,144] circulating microRNAs (miRNAs) and tissue resident miRNAs play paradoxical role both as anti-fibrotic [145][146][147][148] and profibrotic [149][150][151].…”
Section: Messenger Rna Regulatory Network May Modulate Cellular Strementioning
confidence: 99%
“…(Andersen et al, 2020). A recent study revealed that the N-terminal β-propeller domain is the hotspot, where most of the clinically linked allelic variants of NUP155 (24 variants) are clustered and present around R391H and L503F mutations(Leonard et al, 2020;Zhang et al, 2016Zhang et al, , 2008). However, it was not clear how this β-propeller domain is affected by these variants.…”
mentioning
confidence: 99%